DEVELOPMENTAL DYSPLASIA OF THE HIP IN OLDER CHILDREN; PROSPECTS OF FUNCTIONAL AND RADIOLOGICAL OUTCOME FOLLOWING A SINGLE STAGE TRIPLE PROCEDURE - Saqib, Muhammad; Salman, Muhammad; Hayat, Sikandar; Khan, Muhammad Ayaz; Ullah, Shakir (Journal of Ayub Medical College Abbottabad, 2019)
Background: Developmental dysplasia of the hip (DDH) is a diverse entity, which range from mild acetabular dysplasia to frank irreducible hip dislocation. Data regarding the safety and efficacy of one stage triple procedure is limited. Our aim was to analyse the mid-term functional and radiological outcome of single stage triple procedure for children with DDH after walking age. Methods This is a prospective case series of 23 patients (26 hips) who were diagnosed as cases of DDH between July 2014 and June 2017. We included patients with age 20 months and above from both genders who underwent the single stage triple procedure of open reduction, femoral and pelvic osteotomy during the three years. Functional and radiological outcome were assessed according to McKay's and Severin's grading systems respectively. Results: Sixteen (69.6%) girls and 7 (30.4%) boys with a mean age of 4.4±1.9 years. The mean follow-up duration was 8.9±3.2 months. The mean preoperative acetabular index (AI) was 40.3º±2.7º which reduced to an average of 23.4º±3.8º at the end of follow-up. Eight (34.8%) of patients achieved grade I (excellent) of McKay's classification and 9 (39.1%) grade II (good). Postoperatively, 22 (95.7%) patients were below grade III and only one (4.3%) patient was in grade IVa. One case of avascular necrosis of femoral head was observed. Conclusions The single stage triple procedure involving femoral and pelvic osteotomies have excellent functional and radiological outcomes, however, avascular necrosis of the femoral head, redislocation and osteoarthritis in long-term are the adverse events associated with the condition. Keywords: Developmental dysplasia of hip; children; outcome; triple procedure; single stage